Peran Aktivitas Pemasaran Media Sosial Instagram dan Ekuitas Merek Terhadap Respon Pelanggan Bhisa - Sulthan Rafi Arissaputra Soebandono; Nurvita Trianasari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Current technological developments occur in various sectors, one of which is marketing with increasing marketing activities carried out on social media such as Instagram. This is influenced by various factors such as the increase in internet users and the time each person uses the internet. In response to this development, as one of the transportation service providers, PT BST with one of its integrated products, namely Bhisa, uses Instagram social media to market its products and services. The use of Instagram with the username Bhisa.id is PT BST's effort to continue to compete with its competitors. This study aims to determine the influence of Social Media Marketing Activities carried out by PT BST on brand awareness, brand image, EWOM, and commitment both directly and indirectly. This study uses a quantitative causal research method by testing survey data from 180 respondents of Bhisa.id Instagram followers. Testing in the study will use the SEM PLS model which will be tested using the Smart PLS 3 application. The results of the study show that the SMMA variable has a positive influence on brand equity consisting of brand awareness and brand image and has a positive and significant effect on customer responses, namely e-WOM and commitment. Furthermore, strong brand equity contributes positively to customer responses, such as E-WOM and commitment to the Bhisa brand. This study concludes that effective marketing strategies on social media, especially Instagram, can increase brand equity and, in turn, generate better customer responses. The recommendation for marketing practitioners is to continue to utilize Instagram as a primary marketing tool and focus on